2015
DOI: 10.5858/arpa.2014-0550-oa
|View full text |Cite
|
Sign up to set email alerts
|

Advocating Nonsurgical Management of Patients With Small, Incidental Radial Scars at the Time of Needle Core Biopsy: A Study of 77 Cases

Abstract: Context Radial scars are benign sclerosing lesions that are routinely excised when diagnosed in a needle core biopsy. Optimal management for patients with incidental and small (≤5 mm) radial scars is uncertain. Objective To assess pathologic upgrade of radial scars diagnosed in needle core biopsy samples and identify a subset of patients who could benefit from conservative management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 18 publications
1
16
1
Order By: Relevance
“…25 On literature review, a 7% average High-risk breast lesion upgrades upgrade rate was reported with a range of 0-16% when radial scar was diagnosed on core needle biopsy (Table 8). 2,3,15,16,19,23,24,44,[106][107][108][109][110][111][112][113][114][115][116][117][118] Our institutional upgrade rate of 16% was higher than the reported average, likely due to our small case volume (n = 25). No statistically significant radiologic differences were seen between upgraded and not upgraded radial scar core needle biopsy groups in our study.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…25 On literature review, a 7% average High-risk breast lesion upgrades upgrade rate was reported with a range of 0-16% when radial scar was diagnosed on core needle biopsy (Table 8). 2,3,15,16,19,23,24,44,[106][107][108][109][110][111][112][113][114][115][116][117][118] Our institutional upgrade rate of 16% was higher than the reported average, likely due to our small case volume (n = 25). No statistically significant radiologic differences were seen between upgraded and not upgraded radial scar core needle biopsy groups in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous research has shown that incidental and small radial scar lesions (o 5 mm) were less likely to be upgraded on excision. 16,110,115 There is no consensus for the management of radial scar without atypia. It may be prudent to recommend conservative excision for radial scar without atypia with radial scar size greater 45 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we were able to safely observe the majority of patients with CSL/RSL, and report a low risk of future breast cancer development at a median follow‐up of 2.2 years. This is consistent with the recent report by Matrai et al of 77 radial scar lesions under 0.5 cm diagnosed by core biopsy, of which 47% were deemed concordant and the observed upgrade rate to DCIS or invasive carcinoma was 0%. In addition, all subsequent ipsilateral cancers appeared unrelated to the prior CSL/RSL, found at locations 3 cm or more from the initial CSL/RSL core biopsy site.…”
Section: Discussionsupporting
confidence: 93%
“…Historical literature suggests that these lesions are associated with considerable risk of finding breast carcinoma in adjacent tissue, prompting recommendation for excision . The reported incidence of malignancy on excisional specimens following a diagnosis of CSL/RSL on core needle biopsy varies widely, between 0% and 23% …”
Section: Introductionmentioning
confidence: 99%